Miroslav Válek: Three Stages of Canonicity - Nádaskay, Viliam (Colloquia, 2024)
The article focuses on the seminal Slovak poet Miroslav Válek (1927–1991) and his place in the Slovak literary canon. It reconstructs Válek’s literary trajectory, from being a poet of individualist and intimate verse who entered Slovak literature during the political thaw and liberalisation, as an important voice of the generation, to a poet who inclined towards long associative poems with political overtones, culminating in his controversial book-length poem in the 1970s, during his no less controversial time as minister of culture of the Slovak Socialist Republic. Based on the critical reception and publishing history of Válek’s poetry, the paper pays attention to shifts and ambiguities in the poet’s position in both the socialist and post-socialist literary canons. Despite certain fluctuations, the basis of his image remains the same, rooted in his own poetic programme, which coincided with the preferred image of a poet’s work at the time: Válek was and remains both a poet and a politician, a poet of inner turmoil, and a poet of social and political being. The difference the paper attempts to describe is that the socialist literary canon did not differentiate between these extremes (at least in official literary criticism), whereas the Slovak post-socialist canon, which is generally sceptical towards political tones in art, makes the distinction clearly.